2018
DOI: 10.1016/j.bioelechem.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

The second phase of bipolar, nanosecond-range electric pulses determines the electroporation efficiency

Abstract: Bipolar cancellation refers to a phenomenon when applying a second electric pulse reduces ("cancels") cell membrane damage by a preceding electric pulse of the opposite polarity. Bipolar cancellation is a reason why bipolar nanosecond electric pulses (nsEP) cause weaker electroporation than just a single unipolar phase of the same pulse. This study was undertaken to explore the dependence of bipolar cancellation on nsEP parameters, with emphasis on the amplitude ratio of two opposite polarity phases of a bipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…The pulse shapes typically used in whole heart 29 and single cell experiments 58 are approximately trapezoidal, with rise and fall time in the range of 5-20% of the pulse duration; we do not expect that differences in pulse shape are responsible for substantial changes in stimulation results as those already discussed.…”
Section: Reconciling Whole Heart and Isolated Myocyte Resultsmentioning
confidence: 69%
“…The pulse shapes typically used in whole heart 29 and single cell experiments 58 are approximately trapezoidal, with rise and fall time in the range of 5-20% of the pulse duration; we do not expect that differences in pulse shape are responsible for substantial changes in stimulation results as those already discussed.…”
Section: Reconciling Whole Heart and Isolated Myocyte Resultsmentioning
confidence: 69%
“…This is analogous to the phenomenon of bipolar cancellation whereby the application of a second nanosecond pulse of opposite polarity can attenuate or abolish a cellular response (Ca 2+ transient, electronanoporation, fluorescent dye uptake, etc.) triggered by the corresponding unipolar pulse [25][26][27][28][29][30][31][32][33].…”
Section: Plos Onementioning
confidence: 99%
“…One plausible hypothesis is that twin NEPs produced a transient suppression of the number of active channels through perturbations of the lipid bilayer closely interacting with the channel protein. This suggestion is based on a number of indirect observations from our group and others: 1) theoretical molecular dynamics studies [34][35][36] demonstrated that high intensity NEPs are capable of triggering the formation of hydrophilic nanopores in the phospholipid bilayer that lower the energy barrier for ion conduction across the membrane; 2) single or multiple NEPs of various durations are known to cause important perturbations of the lipid bilayer, a process called electronanoporation, that allows the membrane to become permeable not only to ions [37,38] but in some cell types also to fluorescent organic molecules such as propidium iodide and YO-PRO-1 [25,26,29,33,[38][39][40][41][42]. Even though the application of up to ten 5 ns pulses does not lead to YO-PRO-1 uptake in chromaffin cells [23], a non-selective membrane conductance (I leak ) permeable to Na + could be elicited by a single 5 ns pulse in chromaffin cells clamped near the resting membrane potential (-70 mV) in these cells [5], which has also been detected for longer NEPs in GH3 and NG108 cells [7,8] and also in bovine chromaffin cells [8].…”
Section: Plos Onementioning
confidence: 99%
“…Similarly, traditional effects of nsPEF were cancelled by the exposure to asymmetric bipolar nsPEF when the amplitude and the duration of the second pulse were reduced to 35% [2] and 33% [10] of the front pulse, respectively. Recently, Pakhomov et al [11] evaluated the efficiency of electroporation as a function of the second phase of the bipolar nsPEF with durations between 200 ns and 830 ns. It was evident that maximum cancellation, or in other words the least electroporation, occurred when the amplitude of the pulse's second polarity was 50% of the first polarity.…”
Section: Introductionmentioning
confidence: 99%
“…Results of these studies strongly suggest that duration, amplitude, and delay of the reversed second pulse play an important role in determining the efficacy of cancellation. However, despite several formulated hypothesis [11], the mechanism responsible for cancellation is still under investigation. In addition, bipolar cancellation is characteristic of the nanosecond range, as it was not observed in conventional electroporation.…”
Section: Introductionmentioning
confidence: 99%